Factors affecting visual outcome of myopic choroidal neovascularization treated with verteporfin photodynamic therapy - Tan, Colin S. (International Journal of Ophthalmology Press, 2013)
AIM: To evaluate the visual outcomes of choroidal neovascularization (CNV) secondary to pathological myopia and the impact of novel risk factors affecting the final visual outcome. METHODS: Interventional case series of 18 consecutive patients with pathological myopia treated with photodynamic therapy (PDT). Inclusion criteria were spherical equivalent -6D or worse or features of pathological myopia on retinal examination. The main outcome measure was final best-corrected visual acuity (BCVA). RESULTS: Of 18 eyes, 13 (72.2%) avoided moderate visual loss (≥3 lines of LogMAR BCVA) and 5 eyes (27.8%) improved by at least 1 line after 1 year. Patients with LogMAR BCVA ≤0.3 (Snellen equivalent 20/40) at one year were younger than those with BCVA >0.3 (mean age 39.0 vs 61.6 years, P=0.001). A higher proportion of eyes with greatest linear dimension (GLD) of ≤1000µm avoided moderate visual loss (100% vs 50%, P=0.026). Among patients who were treated within 2 weeks of visual symptoms, 88.9% avoided the loss of 3 or more lines compared to 55.6% for those who presented later. The mean improvement in LogMAR BCVA of those with GLD ≤1000µm was +0.12 compared to a loss of 0.55 LogMAR units for those with GLD >1000µm (P=0.02). Visual outcomes were not associated with gender or refractive error. CONCLUSION: Good visual outcome in myopic CNV is associated with younger age, smaller lesion size and earlier initiation of treatment. These factors are relevant for ophthalmologists considering treatment options for myopic CNV.